Animal hoarding cases in England: Implications for public health services - Wilkinson, Justine; Schoultz, Mariyana; King, Helen M.; Neave, Nick; Bailey, Catherine (Frontiers in Public Health, 2022)
Hoarding disorder is characterised by an accumulation of possessions due to excessive acquisition or difficulty discarding , regardless of their actual value and affects 2 – 6% of the population. Animal hoarding, a subset of hoarding disorder, has a significant public health impact. Individuals exhibit self-neglect, apathy, social withdrawal and object hoarding; living within squalid, deteriorated, structurally unsafe and uninhabitable premises, alongside neglected animals. Cases are complex, costly, and impact on a range of service providers. Effective case management is poorly understood and researched, with published literature in England particularly sparse. Improving understanding of the characteristics of these cases is the first step in informed case management. This research is the first exploration of the characteristics of animal hoarders in England and the areas where cases were located. Publicly available information from 66 media reported prosecutions involving large numbers of animals between January 2015 and December 2020 were obtained. Geospatial analysis exploring characteristics of locations where animal hoarding cases are also reported. Findings are consistent with the international literature in that females (64%), those living alone (71%) and those with a mean age of 49 were well represented. Cats (61.5%) and dogs (60%) were the most commonly hoarded species. There was a mean of 44 animals per case. Cases were found in urban, densely populated, and with high levels of deprivation . Animal hoarding raises serious implications for Public Health Services, and the lack of current effective case management strategies are discussed.